2020
DOI: 10.1177/1359105320947790
|View full text |Cite
|
Sign up to set email alerts
|

Patient activation in adults with chronic conditions: A systematic review

Abstract: Patient activation is an important aspect of self-management for adults with chronic non cancerous health conditions (CHC). However, there is limited evidence about which measures of patient activation and healthrelated quality of life are most useful to clinicians. This systematic review examined regarding the types of measures used to evaluate a patient’s readiness for self-management including patient activation and healthrelated quality of life (HRQOL). Two such as measurements are the Patient Activation M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 39 publications
7
35
1
1
Order By: Relevance
“…We found that older age was independently associated with low activation. Similar findings have been reported in diabetes 8 and other chronic diseases, 4,7,8 and our data support research in CKD by Van Bulk et al 32 in dialysis patients and Zimbudzi et al 19 in non‐dialysis CKD. Data from the UKRR 12 found those aged 25‐44 and those who received transplant had the highest activation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found that older age was independently associated with low activation. Similar findings have been reported in diabetes 8 and other chronic diseases, 4,7,8 and our data support research in CKD by Van Bulk et al 32 in dialysis patients and Zimbudzi et al 19 in non‐dialysis CKD. Data from the UKRR 12 found those aged 25‐44 and those who received transplant had the highest activation.…”
Section: Discussionsupporting
confidence: 93%
“…We found patients with low activation had lower cardiorespiratory fitness and HRQOL. This supports a plethora of research in older adults and LTCs 4,7–9 . In CKD, data from the UKRR 12 found those who reported better HRQOL had higher activation levels.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…13 Thus, activating adults with chronic non-communicable diseases for patient participation in selfmanagement activities is essential for improving overall health and HRQOL. 14 In a systematic review that identified, through 36 articles, the variables that most influenced the HRQOL of people on renal dialysis, the variable activation was not used. 15 In addition, studies associating patient activation with HRQOL in people with CKD are limited 16,17 and, when considering people on hemodialysis treatment, are even more restricted.…”
Section: Introductionmentioning
confidence: 99%